Strategic decision behavior and audit quality of big and small audit firms in a tendering process - Martin Fochmann; Marcel Haak (Arbeitskreis Quantitative Steuerlehre (arqus), 2015)
We investigate the strategic decision making of audit firms in a tendering process. In particular, we are interested in how audit firms behave to acquire audit clients and which audit quality is ensured. Our main findings are manifold. First, if two big audit firms are competing, we do not observe that each firm tries to acquire all clients. However, if one big and one small audit firm are competing, we find evidence that the big audit firm generally apply strategies to acquire all available clients. In contrast, the small audit firm uses a clear "Guerilla Strategy" which means that the firm concentrates only on few clients whereas the other clients are almost ignored. Second, small audit firms are better off if more clients do exist in the tendering process. Thus, the legislator should ensure that more audit clients are tendered if the competitiveness of smaller audit firms should be enhanced. Third, in a situation in which the competitive advantage of big audit firms increases over-proportionally, we do not observe that big audit firms are able to decrease the market share of small audit firms markedly or are even able to push small audit firms out of the market. Fourth, we find that the quality level of an audit is higher if the client is acquired by a small audit firm. This implies that increasing the number of smaller audit firms could increase the quality level of the audit market.
Keywords: M42; C91; 330; tendering process; behavioral accounting; experimental economics